The biosecurity risks of seeds in a botanic garden context - Sara Redstone; Adrian Fox (Sibbaldia, 2021)
Seeds present a naturally occurring package of germplasm with ideal attributes for collection, distribution and, in the case of orthodox seed, long term storage. From a phytosanitary perspective seeds are often considered a relatively low-risk option for movement of germplasm across borders. Most published data are concerned with diseases of commercial crops and little is known about the risks associated with wild collected, non-commercial seeds. However, there is demonstrable risk associated with the movement of any plant germplasm which can pose a risk to both crops and the wider environment. Presented here are a discussion on seed standards and the difference between seed borne and seed transmitted pathogens, with case studies presented to highlight the risks associated with informal seed systems and wild collected seeds in particular. Additionally, suggestions on how to address phytosanitary issues are presented including awareness raising measures aimed at improving biosecurity procedures during collection and before long-term storage of seed accessions.